A Study on Benefits, Challenges and Factors Impressing Customer Relationship Management (CRM) W.R.T. Private Commercial Banks at Bengaluru - Dr. Lokesh G R; Harish K S; Dr. Geethanjali G (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2023)
Purpose: The main end of the present paper is to know whether the socio-economic characteristics impress on the CRM and to know the benefits of CRM, factors driving CRM, and challenges faced by the private commercial banks at the time of implementation of CRM. The presence of severe competition where the competitive struggle to claim a larger share and to attract major amount of customers, forces the banking companies to install CRM strategies and to fetch better results. It has been felt as a process aimed at collecting customer data, find profile of customers and use the knowledge of the customers in a particular marketing activities (Anu Putney et al. 2013) CRM is the strongest and most efficient approach in maintaining and treating close relationship with customers (Angumuthu, 2015). CRM is a management approach that seeks to create, develop and widen relationship with customers in order to derive maximum customer value, profits and shareholders value (Mallika Srinivastava, 2012). Approach: A designed questionnaire was steered as schedule in order to avoid any unexpected delay, incompleteness and non-response. Respondents were approached while they are in the bank premises either before or after their bank work, in a natural setting. A total of 217 questionnaires were in the hand and out of 217, only 200 were usable one and the remaining discarded forming 92% success rate. Chi-square, contingency co-efficient, Kendall’s co-efficient concordance weighted average, Garrett ranking technique was performed to analyse and present the data. Findings: The study revealed about the presence of favourable socio-economic characteristics revealing a significant and high relationship between the characteristics and CRM except bank at different branches which showed less significant and low degree and benefits include protection of data privacy, enhanced productivity and boosted sales. Further, the study also reveals about the factors like advanced technology, customer centric approach and safety factors driving CRM in private commercial banks. The challenges faced at the time of implementation of CRM includes choosing the right CRM, data security and time and cost of implementation of software.